Evidence of Human Exposure to Tamdy Virus, Northwest China - Moming, Abulimiti; Shen, Shu; Fang, Yaohui; Zhang, Jingyuan; Zhang, Yanfang; Tang, Shuang; Li, Tianxian; Hu, Zhihong; Wang, Hualin; Zhang, Yujiang; Sun, Surong; Wang, Lin-Fa; et al. (Emerging infectious diseases, 2021)
We report the isolation of Tamdy virus from Hyalomma asiaticum ticks in northwest China and serologic evidence of human Tamdy virus infection in the same region. These findings highlight the need to further investigate a potential causal relationship between Tamdy virus and febrile illnesses of unknown etiology in that region.